2016
DOI: 10.3892/etm.2016.3060
|View full text |Cite
|
Sign up to set email alerts
|

Time course of various cell origin circulating microparticles in ST-segment elevation myocardial infarction patients undergoing percutaneous transluminal coronary intervention

Abstract: Abstract. The present study aimed to investigate the time course of changes in microparticles (MPs) in patients with ST-segment elevation myocardial infarction (STEMI) that underwent percutaneous transluminal coronary intervention (PCI). A total of 24 STEMI patients undergoing primary PCI were enrolled, and circulating MPs were detected immediately prior to and after PCI, and at 4, 24 and 48 h post-PCI. Standard Megamix beads, based measurement protocols, were employed to measure MPs of different cell origin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Furthermore, it has been reported that the numbers of circulating MPs continued to increase in the short term following appropriate intervention in STEMI patients. Zhou et al [117] followed up circulating levels of MPs over time in STEMI patients undergoing percutaneous transluminal coronary intervention (PCI) (before and up to 48 h after PCI). The authors found that platelet MPs increased directly after the PCI and continued to rise over time until the end of follow-up period, whereas the levels of leukocyte- and endothelial-derived MPs decreased after the PCI, but rose thereafter until the end of the follow-up period [117].…”
Section: Pathophysiological Roles Of Mps In Altering Cell Signalinmentioning
confidence: 99%
“…Furthermore, it has been reported that the numbers of circulating MPs continued to increase in the short term following appropriate intervention in STEMI patients. Zhou et al [117] followed up circulating levels of MPs over time in STEMI patients undergoing percutaneous transluminal coronary intervention (PCI) (before and up to 48 h after PCI). The authors found that platelet MPs increased directly after the PCI and continued to rise over time until the end of follow-up period, whereas the levels of leukocyte- and endothelial-derived MPs decreased after the PCI, but rose thereafter until the end of the follow-up period [117].…”
Section: Pathophysiological Roles Of Mps In Altering Cell Signalinmentioning
confidence: 99%
“…In the setting of acute coronary syndromes, the most studied microparticles are platelet derived microparticles and endothelial derived microparticles. Observational studies showed increased levels of CD146+ and CD31+ endothelial derived microparticles ( microparticles decreased immediately post PCI and gradually increased up to 48 hours later (264). Abciximab, an GPIIb-IIIa antagonist, in combination with primary coronary angioplasty reduces the level of platelet derived microparticles compared with patients that had only percutaneous angioplasty (261).…”
Section: Acute Coronary Syndromesmentioning
confidence: 99%